2001
DOI: 10.1073/pnas.081474898
|View full text |Cite
|
Sign up to set email alerts
|

Skp2 is oncogenic and overexpressed in human cancers

Abstract: Skp2 is a member of the F-box family of substrate-recognition subunits of SCF ubiquitin-protein ligase complexes that has been implicated in the ubiquitin-mediated degradation of several key regulators of mammalian G1 progression, including the cyclindependent kinase inhibitor p27, a dosage-dependent tumor suppressor protein. In this study, we examined Skp2 and p27 protein expression by immunohistochemistry in normal oral epithelium and in different stages of malignant oral cancer progression, including dyspla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
388
3
13

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 456 publications
(424 citation statements)
references
References 30 publications
(38 reference statements)
20
388
3
13
Order By: Relevance
“…First, we show that both Skp2 and Cks1 expression is enhanced in human melanoma cells lines compared to melanocytes. Enhanced levels of Skp2 have been associated with several types of human cancer (Gstaiger et al, 2001) and, during the course of our work, have been detected in melanoma tissue sections (Li et al, 2004;Woenckhaus et al, 2005). Also, Cks1 levels are enhanced in non-small cell lung and colorectal carcinoma (Inui et al, 2003;Shapira et al, 2004).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…First, we show that both Skp2 and Cks1 expression is enhanced in human melanoma cells lines compared to melanocytes. Enhanced levels of Skp2 have been associated with several types of human cancer (Gstaiger et al, 2001) and, during the course of our work, have been detected in melanoma tissue sections (Li et al, 2004;Woenckhaus et al, 2005). Also, Cks1 levels are enhanced in non-small cell lung and colorectal carcinoma (Inui et al, 2003;Shapira et al, 2004).…”
Section: Discussionsupporting
confidence: 55%
“…Structural analysis indicates that p27 Kip1 interacts with both Cks1 and Skp2 (Hao et al, 2005). Knockout of either Skp2 or Cks1 in mice leads to increased p27 Kip1 levels (Nakayama et al, 2000;Spruck et al, 2001) and, notably, expression of Skp2 and Cks1 is enhanced in several cancers (Gstaiger et al, 2001;Latres et al, 2001;Inui et al, 2003;Shapira et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…3). In particular, Skp2 levels have been examined in human tumors and have been shown to correlate with grade of malignancy [51,[53][54][55][56][57]69,70]. Similar findings have been reported for high levels of cyclin E and A (reviewed in [58]).…”
Section: P27 and Human Cancersmentioning
confidence: 69%
“…Immunohistochemical studies revealed that high levels of Skp2 and low levels of p27 correlate with high grade malignancy in lymphomas [53]. Moreover, investigations of oral tissues have shown that Skp2 levels are elevated in epithelial adenomas and continue to increase during progression to carcinomas [54], while expression of Skp2 correlates with poor prognosis of oral cancer [51]. Recent studies have shown that Skp2 is overexpressed in breast carcinomas that are negative for both the estrogen receptor (ER) and Erb2-neu [57].…”
Section: P27 and Human Cancersmentioning
confidence: 99%
“…Overexpression or Regulation of RASSF1A by Skp2 at G 1 -S transition MS Song et al amplification of Skp2 has been reported in a large number of human cancers (Yokoi et al, 2002) and transgenic expression of Skp2 in mice leads to tumor formation, suggesting that Skp2 is oncogenic (Gstaiger et al, 2001;Latres et al, 2001). Skp2 targets p27, cyclin E and FOXO1 for degradation in a phosphorylationdependent manner (Marti et al, 1999;Nakayama et al, 2000;Huang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%